Peering into the black box. (Economist, 2018)
The article explores the ability of artificial intelligence (AI) to perform the tasks previously done by human beings. It cites the use off AI in medical diagnosis, insurance and self-driving cars. The ability of machine learning to give computers the ability to train themselves is discussed. In addition, the article explains the struggle of people to understand how computer programs work.